Hubungan Tingkat Kecemasan Pada Masa Pandemi Covid-19 Dengan Kualitas Hidup Lansia Di Panti Sosial Tresna Werdha Budi Mulia 1 Cipayung Di Jakarta Timur - Afriaty Afriaty; Nita Sukamti; Milla Evelianti (MAHESA : Malahayati Health Student Journal, 2022)
ABSTRACT Covid-19 is a pandemic that poses a global health threat, especially for individuals who are susceptible to infection, such as the elderly. From a preliminary study in nursing homes for the elderly, many complained about living their lives during the pandemic because no one visited which made the elderly feel lonely, causing anxiety and disrupting their quality of life. To identify the relationship between anxiety level during covid-19 pandemic with quality of life among elderly in tresna werdha budi mulia 1 retirement home Cipayung. Correlative Descriptive Research on the Elderly at Tresna werdha Budi Mulia 1 retirement home Cipayung. The sampling technique was carried out by purposive sampling with a total of 72 respondents. This research instrument uses. The statistical test used is the Spearman rank test with a significant level of 0.05. The results of the study showed the majority of 65.3% of respondents had a moderate level of anxiety and 76.4% had a good quality of life. Spearman rank test results obtained Rs of -0.349 (p-value: 0.003) which can be concluded that there is a relationship between anxiety levels and the quality of life of the elderly at Budi Mulia 1 retirement home Cipayung. Most of the elderly at Budi Mulia 1 retirement home Cipayung have moderate levels of anxiety and good quality of life. There is a relationship between the level of anxiety with quality of life. The caretaker of the nursing home should make efforts to increase the motivation of the elderly to live, by carrying out activities in the orphanage that can increase their motivation and enthusiasm in living life in the home for the elderly during the Covid-19 pandemic. Keywords: Elderly, Anxiety Level, Quality Of Life, Covid-19 ABSTRAK Covid-19 sebagai pandemi yang memberikan ancaman kesehatan secara global, terutama pada individu yang rentan untuk tertular seperti lansia. Dari studi pendahuluan di Panti lanjut usia banyak yang mengeluh dalam menjalani kehidupan selama pandemi karena tidak ada yang berkunjungan yang membuat lansia merasa kesepian mengakibatkan cemas dan membuat kualitas hidupnya terganggu. Tujuan penelitian ini untuk mengetahui hubungan tingkat kecemasan pada masa pandemi Covid-19 dengan kualitas hidup lansia di Panti Sosial Tresna Werdha Budi Mulia 1 Cipayung. Penelitian Deskripstif Korelatif pada lansia di Panti Wredha Budi Mulia 1 Cipayung. Teknik pengambilan sampel dilakukan dengan cara purposive sampling dengan Jumlah 72 responden. Instrument penelitian ini menggunakan. Uji statistic yang digunakan adalah uji rank spearman dengan tingkat signifikan 0,05. Hasil penelitian mayoritas 63,5% responden memilki tingkat kecemasan sedang dan 76,4% memiliki kualitas hidup baik. Hasi uji rank spearman diperoleh Rs sebesar -0,349 (p-value : 0,003). Lansia di Panti Wredha Budi Mulia Cipayung sebaian besar memiliki tingkat kecemasan sedang dan kualitas hidup baik. Terdapat hubungan antara tingkat kecemasan dengan kualitas hidup. Pengurus panti wredha hendaknya melakukan upaya-upaya untuk meningkatkan motivasi hidup lansia, dengan melakukan kegiatan-kegiatan rekresiasi di dalam panti wredha, sehingga lansia tidak merasa bosa selama Pandemi Covid-19 dapat meningkatkan motivasi dan semangatnya dalam menjalani hidup di panti wredha selama Pandemi Covid- 19. Kata Kunci: Lansia, Tingkat Kecemasan, Kualitas Hidup, Covid-19